2019
DOI: 10.1126/scitranslmed.aau6934
|View full text |Cite
|
Sign up to set email alerts
|

Bioengineered human acellular vessels recellularize and evolve into living blood vessels after human implantation

Abstract: Traditional vascular grafts constructed from synthetic polymers or cadaveric human or animal tissues support the clinical need for readily available blood vessels, but often come with associated risks. Histopathological evaluation of these materials has shown adverse host cellular reactions and/or mechanical degradation due to insufficient or inappropriate matrix remodeling. We developed an investigational bioengineered human acellular vessel (HAV), which is currently being studied as a hemodialysis conduit in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
134
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 174 publications
(147 citation statements)
references
References 67 publications
3
134
1
Order By: Relevance
“…"Lifeline" grafts were disappointing though they were few. "Humacyte, " in contrast, had 60 access grafts implanted at 6 centers (325,326) and 20 femoro-popliteal grafts at 3 centers (327). Primary patencies were low both in the access grafts and in the femoro-popliteal grafts.…”
Section: Native and In-vitro Grown Natural Matricesmentioning
confidence: 99%
“…"Lifeline" grafts were disappointing though they were few. "Humacyte, " in contrast, had 60 access grafts implanted at 6 centers (325,326) and 20 femoro-popliteal grafts at 3 centers (327). Primary patencies were low both in the access grafts and in the femoro-popliteal grafts.…”
Section: Native and In-vitro Grown Natural Matricesmentioning
confidence: 99%
“…Macrophages play a pivotal role in the initiation and perpetuation of inflammation and remodeling processes, thereby determining either the chronicity or the resolution of the inflammatory process-and this has been demonstrated also for tissue-engineered implants such as vascular grafts [12][13][14][15][16][17][18] . In these studies, M2 macrophages were shown to help the recruitment of tissue remodeling cells (e.g.…”
mentioning
confidence: 99%
“…Notwithstanding reports of promising results (McAllister et al 2009;Syedain et al 2017;Kirkton et al 2019), cell-based strategies remain limited by the absence of protocols for the rapid and scalable production of patient-specific vascular wall cells and need for decellularization before implantation (Wystrychowski et al 2014;Lawson et al 2016). More specifically, studies have revealed feasibility challenges when using cells isolated from the intended patient population (>65 years old), or allogeneic sources, including reduced proliferation and ECM production due to telomere shortening (Poh et al 2005), and immune rejection associated with HLA mismatching.…”
Section: Structural Considerations In Vascular Graftsmentioning
confidence: 99%